Expanded character sampling underscores phylogenetic stability of Ardipithecus ramidus as a basal hominin. Issue 131 (June 2019) - Mongle, Carrie S.; Strait, David S.; Grine, Frederick E.
Abstract: Phylogenetic relationships among hominins provide a necessary framework for assessing their evolution. Reconstructing these relationships hinges on the strength of the character data analyzed. The phylogenetic position of Ardipithecus ramidus is critical to understanding early hominin evolution, and while many accept that it is most likely the sister taxon to all later hominins, others have argued that Ar. ramidus was ancestral to Pan . Although the study by Strait and Grine (2004) suggested the former, available evidence permitted only 26% of characters in their matrix to be assessed for Ar. ramidus . Fossils described subsequently by Suwa, White and colleagues in 2009 have enabled the number of characters that can be coded for this species to be expanded to 78% of the matrix. Here, we incorporate these new character data to evaluate their impact on the phylogenetic relationships of Ar. ramidus . Moreover, we have further revised the Strait and Grine (2004) matrix as necessitated by additions to the hypodigms of other fossil taxa. This updated matrix was analyzed using both parsimony and Bayesian techniques in a sequence of four iterative steps to independently evaluate the impact of matrix and expanded character revisions on tree topology. Despite the new data and matrix revisions, tree topology has remained remarkably stable. The addition of new craniodental material has served to markedly strengthen the support for the placement of Ar. ramidus as being derived relative to Sahelanthropus, and as the sister taxon of all later hominins . These findings support the phylogenetic hypothesis originally proposed by White and colleagues in 1994. This updated matrix provides a basis for the assessment of additional extinct species.